Imaging Patterns of Recurrent Infarction in the Mechanisms of Early Recurrence in Intracranial Atherosclerotic Disease (MyRIAD) Study - Sangha, Rajbeer S.; Prabhakaran, Shyam; Feldmann, Edward; Honda, Tristan; Nizam, Azhar; Cotsonis, George A.; Campo-Bustillo, Iszet; Romano, Jose G.; Liebeskind, David S. (Frontiers in Neurology, 2021)
Introduction: While much is known about recurrent clinical events in patients with intracranial atherosclerotic disease (ICAD), there is limited data on characteristics of recurrent infarcts. Methods: The NIH-funded MyRIAD prospective, observational study was designed to identify mechanisms of ischemia and predictors of recurrence in ICAD. Recurrent infarction was assessed on MRI at 6–8 weeks. We reviewed the DWI/ADC and FLAIR sequences in patients with recurrent stroke and characterized the number of infarcts, infarct location, size, and patterns based on whether they were borderzone (BZ), perforator (SC/P), cortical or territorial (C/T), and mixed. Temporal characteristics were delineated by ADC/FLAIR correlation. Results: Of the 89 patients with 6–8 weeks MRI, 22 (24.7%) had recurrent infarcts in the territory of the symptomatic artery. Recurrent infarcts were evident on DWI in 63.6% and single infarcts in 54.5%. The median recurrent infarct volume was 2.0 cm3 compared to median index infarct volumes of 2.5 cm3. A mixed infarct pattern was most common (40.9%), followed by borderzone (22.7%), cortical or territorial (27.3%), while only 9.1% were in a perforator artery distribution. Amongst those with a mixed pattern, 8/9 had a borderzone distribution infarct as part of their mixed infarct pattern. Conclusion: These findings provide novel data on the characteristics of early recurrent infarcts in patients with symptomatic ICAD.